An evaluation of the millennium development goals and their impact on education - Carrillo Flores, Isabel (2016)
This article analyses the status of education as a fundamental right. The recenteconomic crisis and associated austerity policies have worsened the situation and,rather than diminish, educational inequalities have in fact increased. Firstly, thesignificance of education as a Human Right is examined. Secondly, the extentto which the MDGs have been met is reviewed, particularly with regard toeducation, where, as detailed in various reports produced by NGOs and by theUnited Nations, certain difficulties have impeded their being met. The Right toEducation is examined in a projective way as a right that should not be limitedto the vision contained in the new Sustainable Development Goals for 2030.It is necessary to go still further and advance towards a true democratisation ofeducation.